(3fXQjI GdJWhQ (B:s (3GdOYGhi hGdQO (B: 50 (3SDGdG hLhGHG (B/s - (3WdYJ, gjKes ((3LeghQjI eUQ GdYQHjI (B:s (3JHUjQ ddfTQ hGdJhRjY ,s, 2019)
(3gPG GdcJGH def jQjO Cf jUd Edi GdMb UGajG HdG ThGFH, QGSNG HdG eZGdWGJ, gPG GdcJGH def dG jDLQhf Ybhdge Edi YbdjI GdbWjY hdcfge jOhQhf eY GdOdjd MjK OGQ(B. (3fXQjI GdJWhQ gj Mde jJefGg GdedMOhf hjMQUhf Ydi GdJCSjS dg Hcd GdSHd, aGdedMO jQjOgG JWhQG, dCf GdcGFfGJ GdMjI Ydi hLg GdCQV EeG fJGL Ndb eHGTQ Ch fJGL JWhQ hdG HOjd KGdK hefP CcKQ ef bQf ef GdReGf jMGhd GdedMOhf HYTQGJ GdJNejfGJ OYe GdfXQjI, dcfgG(B-(3hjG ddYLH(B-(3JHbi MJi GdSGYI JUhQG hMdeG jOGYH Ybhd GdHYV Ohf Odjd jMSe GdLOGd (B! (3aj gPG GdcJGH jJYQV GdeDda dCTgQ OYGhi Gdbhe hCMdGege hSjchf GdajUd aj JeMjU gPg GdOYGhi hGdCMdGe gh GdHQgGf GdYdej hGdfbO GdYbdj dG GdJMjRGJ GdeSHbI hGdGJgGeGJ GdeJSQYI(B. (3jJejR GdcJGH HJhKjb GdeQGLY hGdChQGb GdYdejI HGdUhQI ef GdeQGLY eHGTQI MJi jchf COYi ddJMbb ef UMI GdeYdheI hJhKjb GdHQgGf CeGe Yjfj GdbGQF hcJH GdcJGH aj gjFI SDGd hLhGH ; djchf COYi ddGfJHGg hGdJQcjR hGdJPcQ hSghdI GSJMVGQ GdeYdheI(B. s
(3GdcJGH ehKb HGdeQGLY GdYdejI eUhQI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdEdMGO hGdedMOhfs -- (3fXQjI GdJWhQs -- (3CSFdI hCLhHI s; (3GdfThA hGdGQJbGAs -- (3fXQjI OGQhjfs